(3JegjO GdbhGYO TQM JSgjd GdahGFOs - (3eMH GdOjf eMeO Hf jhSa Hf CMeO GdMdHj GdeUQj GdeYQha H`` fGXQ GdLjTs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3GdeOQSI GdefUhQjI HGdbGgQI s)
(3ChdgG (B:s
(3bGd HGH GdCaYGd GdQGaYI GdGSe, GdfGUHI GdNHQ cGf hCVMi hCUHM hCeSi hXd hHGJ hUGQ hdjS s
(3BNQgG (B:s
(3dCfgG UGQJ HefRdI (B"(3eY(B" (3h(B"(3eY(B" (3dG JfaUd HjfgG hHjf eLQhQgG GdMeO ddg jJdhg aj GdKGdK HGH GdeSJKfi s
(3ocJHJ Hbde eged GdfbW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3HgG CKQ JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs